Building Effective Communication Between Teachers and Early Children In PAUD Institutions - Ditha Prasanti; Dinda Rakhma Fitriani (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2018)
Effective communication is certainly the dream of everyone who does it. Not separated from the communication process, early childhood also interacts to achieve the desired communication goals. In this article, the author discusses the efforts to build effective communication for teachers and early childhood in the X PAUD institution in Bandung. The author sees this topic as very important because it is an urgency now to express the creation of effective communication between teachers and early childhood in their PAUD institutions. This study uses a qualitative approach to the case study method. The author raises a case about efforts to build effective communication in the PAUD X institution. This study is very suitable to be analyzed with symbolic interaction theory because there is a meaning in the communication process conducted by teachers with early childhood in the PAUD institution. The results showed that there were efforts made to build effective communication between teachers and early childhood, including: (1) PAUD teachers as communicators must have characteristics of patience, willingness to sacrifice, attention, assertiveness, and be able to attract early childhood attention; (2) the existence of media / tools used by PAUD teachers at the X institution to achieve effective communication for teachers and early childhood; (3) PAUD teachers must understand the diverse character of their students